Hubungan pola makan dengan pengendalian kadar glukosa darah pengidap diabetes melitus tipe 2 rawat jalan di RSU Gunung Jati Cirebon - Juleka Juleka; Ahmad Husain Asdie; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2005)
Background: Diabetes Mellitus (DM) is a chronic disease which has increasing prevalence today. The result of epidemiological study in Indonesia showed that DM prevalence was 1,5-2,3% to population aging over 15 years. DM disease cannot be cured but can be controlled to slow down the complications. Consumption planning is a major component in DM management. there are 3 main principles applied in the supply of food to diabetics, i. e. number of calories, type of food and meal schedule. Observation result shows that over 50% of diabetics do not follow the suggested consumption planning.Objective: The purpose of the study was to investigate the relationship between eating pattern and control of glucose to type 2 diabetics patients.Methods: The study was an analytic observational type using cross sectional design. Purposively taken samples were diabetic type 2 inpatients at Gunung Jati Hospital, Cirebon. Glucose of type 2 diabetics was determined through examination of glucose during fasting and 2 hours post prandial using enzymatic method gained from medical assessment data, and eating pattern gained from 24 hours recall method for 4 days. To know the relationship between eating pattern and control of glucose to type 2 diabetics, chi square, odds ratio (OR) signifi cance and logistic regression were tested.Results: There was relationship between energy (OR=31.6,CI=5.00-199.76), carbohydrate (OR=12.7,CI=1.30-124.3) and fat (OR=5.20, CI=1.08-24.89) intake with glucose control of type 2 diabetics, there was relationship between sugar consumption and process result (OR=13.1, CI= 2.59-66.2) of vegetables (OR=31.6, CI=3.74-267.6) and fruits (OR=5.16, CI=1.41-18.91) with glucose control, there was no relationship between protein intake and meal schedule with glucose control of type 2 diabetics.